Natural habitats of typical plants growing on ruins of Roman archaeological sites (Rome, Italy). (2nd September 2016) - Ceschin, S.; Bartoli, F.; Salerno, G.; Zuccarello, V.; Caneva, G.
Abstract : In this study, we support the hypothesis that wall plant species come mainly from rocky habitats, taking into account that ancient walls show similar characteristics to rocks. The occurrence of wall species in natural habitats was investigated. The main literature concerning wall and natural vegetation of central-southern Italy was viewed. Vegetation synoptic tables were analysed through statistical procedures for comparing occurrence and behaviour of wall species in ruderal habitats as archaeological sites and natural ones.The study pointed out that wall species show similar ecological and coenological features in both habitats. This confirms that the main natural habitat from which wall species come from are rocks, but secondarily also ephemeral Mediterranean meadows and garrigues. Particularly, some wall species belonging to Parietarietea judaicae class are participating in the formation of natural rocky communities of Asplenietea trichomanis . Species occurring on emerging ruins form ephemeral meadows belonging to Helianthemetea guttati, also found in natural Mediterranean environment. On wide tops of ruins, where community dynamism is higher, some perennial herbaceous and shrubby species participate in the formation of impoverished communities matching to natural aspects of Mediterranean maquis. The knowledge of the natural habitat of wall species can be useful for a better management of archaeological sites.